2021
DOI: 10.1016/j.biosx.2021.100076
|View full text |Cite
|
Sign up to set email alerts
|

A paper-based colorimetric molecular test for SARS-CoV-2 in saliva

Abstract: Herein, we describe the development of a paper-based device to detect nucleic acids of pathogens of interest in complex samples using loop-mediated isothermal amplification (LAMP) by producing a colorimetric response visible to the human eye. To demonstrate the utility of this device in emerging public health emergencies, we developed and optimized our device to detect SARS-CoV-2 in human saliva without preprocessing. The resulting device was capable of detecting the virus within 60 min and had an analytical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 64 publications
(70 reference statements)
1
75
0
Order By: Relevance
“…From this, it is considered that the qPCR method is highly useful in the future. Recently, the development of a LAMP test using saliva as a sample [10] and an attempt to place a satellite laboratory in the inpatient ward of a COVID-19 patient to perform a rapid test [11] have been reported. Various other test methods have been developed and studied [12][13][14][15][16], but none have achieved the same sensitivity and specificity as the conventional qPCR test.…”
Section: Discussionmentioning
confidence: 99%
“…From this, it is considered that the qPCR method is highly useful in the future. Recently, the development of a LAMP test using saliva as a sample [10] and an attempt to place a satellite laboratory in the inpatient ward of a COVID-19 patient to perform a rapid test [11] have been reported. Various other test methods have been developed and studied [12][13][14][15][16], but none have achieved the same sensitivity and specificity as the conventional qPCR test.…”
Section: Discussionmentioning
confidence: 99%
“…These dyes allow visualization of the result with the naked eye. In the assay presented here, we build on the primers previously designed by us [ 16 ] and couple them with a pH-sensitive colorimetric reagent: phenol red [ 28 ]. The primers were screened through the LOD study.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in previous studies, the Warmstart ® LAMP 2 × Master Mix, which contains phenol red, is characterized by its transition from pink to yellow as the LAMP reaction occurs and the pH decreases [ 28 , 34 ]. Positive and negative results using our selected primers for the detection of P. multocida , M. haemolytica , H. somni , and the pink and yellow distinction can be observed in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we present the fabrication of a paper-based device that uses loop-mediated isothermal amplification (LAMP) to detect nucleic acids of pathogens of interest in complex samples by providing a colorimetric response observable to the naked eye. We have previously demonstrated that this device can be used to detect SARS-CoV-2 in human saliva with a limit of detection of 200 copies/µL saliva [2] . Unlike most nucleic-acid-based biosensors for SARS-CoV-2 detection [ 1 , 3 , 7 ], this device does not require prior RNA extraction or concentration.…”
Section: *Methods Detailsmentioning
confidence: 99%